The loaches of the genus Nemacheilus (Teleostei: Nemacheilidae) in Sunda Islands, with an identification key [Ikan genus Nemacheilus (Teleostei: Nemacheilidae) di Kepulauan Sunda, berikut kunci identifikasinya] - Renny Kurnia Hadiaty; Kazunori Yamahira (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2014)
Loaches of the genus Nemacheilus are distributed in Southeast Asia from the mainland of Asia to Sunda Islands (Sumatra, Java, and Borneo). In this paper, the status of Nemacheilus in Sunda Islands is discussed base on the results of field trips in Indonesian waters, the fish collections in Museum Zoologicum Bogoriense, and published papers. There are 18 species in Sunda Islands, 8 species inhabit in Sumatra and 10 species in Kalimantan, and only 2 species inhabit in Java. An idetification key of the 18 species is also included. Abstrak Ikan genus Nemacheilus tersebar meliputi wilayah Asia Tenggara, dari daratan Asia sampai ke Kepulauan Sunda (Sumatra, Jawa, dan Kalimantan). Dalam tulisan ini dikemukakan status Nemacheilus di pulau-pulau tersebut berdasarkan hasil kegiatan lapangan di perairan Indonesia, koleksi di Museum Zoologicum Bogoriense (MZB), dan tulisan yang te-lah dipublikasi. Di Kepulauan Sunda dijumpai 18 species Nemacheilus, delapan spesies dijumpai di Sumatra, 10 spesies di Kalimantan dan hanya dua spesies di Jawa. Kunci identifikasi 18 spesies Nemacheilus disertakan.